2015
DOI: 10.1002/bse.1909
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Green Products in Air Travel: Ready for Take‐Off?

Abstract: We examine the willingness to pay (WTP) for green products in air travel. Green products in aviation are supplementary services, which are sold on top of the travel service (e.g. carbon offsets, organic on‐board food). We identify a set of potential green products in aviation and report the preferences for additional airline services of 811 Swiss air travellers using an adaptive choice‐based conjoint survey. We find that 20% of those passengers who are interested in purchasing supplementary services show a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 36 publications
3
61
3
Order By: Relevance
“…Testing consumer follow‐through with the TRA in the context of reused/recycled content at different price points is advisable. An understanding of relative pricing is critical for determining the role of postconsumer product recovery in a more sustainable economy, as it allows for setting of prices for products made from either virgin or nonvirgin content. The lack of a statistically significant relationship between knowledge and intent to purchase was unexpected and warrants further consideration as this inconsistent with previous studies (Hinnen et al, ; Paulraj, ). Understanding the decision‐making process and priorities of consumers who do not currently intend to purchase greener products assists in determining appropriate policy levers to change behavior. Also, an understanding of product/price preference is critical for determining the relation between product/material recovery, producing economic value and reducing environmental impact.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Testing consumer follow‐through with the TRA in the context of reused/recycled content at different price points is advisable. An understanding of relative pricing is critical for determining the role of postconsumer product recovery in a more sustainable economy, as it allows for setting of prices for products made from either virgin or nonvirgin content. The lack of a statistically significant relationship between knowledge and intent to purchase was unexpected and warrants further consideration as this inconsistent with previous studies (Hinnen et al, ; Paulraj, ). Understanding the decision‐making process and priorities of consumers who do not currently intend to purchase greener products assists in determining appropriate policy levers to change behavior. Also, an understanding of product/price preference is critical for determining the relation between product/material recovery, producing economic value and reducing environmental impact.…”
Section: Discussioncontrasting
confidence: 65%
“…Attitude influences consumer perceptions of the quality of a product (Cordell, ; Good & Huddleston, ; Kinra, ; Kumar et al, ; Terenggana, Supit, & Utami, ). Attitude toward environmental protection should include attitude toward products with recycled/reused content (Hinnen, Hille, & Wittmer, ). Hence:H5 The relationship between attitude toward environment protection and the perception of quality of products with recycled/reused content is positive.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…Earlier studies showed that customers who have eco‐friendly attitudes have an intention to visit a green hotel and even pay more for a green hotel (Han et al, ; Manaktola & Jauhari, ; Verma & Chandra, ). Hinnen, Hille, and Wittmer () found out that only 20% of customers were willing to pay more for green products and claimed that green customers do not differ from the other customers in terms of demographic and socioeconomic characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides overcoming these limitations, future research could gain advantage by further investigating the relative importance of these attributes—as it is traditionally done in the consumer purchase behavior literature—and by identifying different groups of backers. Indeed, this literature, while documenting a broad interest towards sustainability by individuals and groups, claims that there are great differences among various consumer groups, particularly according to gender, educational level, income, age, and so forth (Torjusen, Lieblein, Wandel, & Francis, ; Ubilava et al, ; Vecchio & Annunziata, : Hinnen, Hille, & Wittmer, ). We expect that these differences towards sustainability will emerge also in the context of CF, that is, among backers.…”
Section: Conclusion Limitations and Future Developmentsmentioning
confidence: 99%